Occurrence State and Properties of Gold Minerals from the Gold Deposits on the North China Platform - Chao, Yuhong; Yin, Jianzhao; Yin, Yuhan; Shi, Hongyun; Xiang, Shoupu (European Journal of Applied Sciences, 2022)
By studying both the microscopic physical and chemical typomorphic characteristics of gold minerals associated with representative gold deposits on the north-central margin of the North China Platform, this paper seeks to identify macroscopic metallogenic mechanisms of gold deposits. The majority of the gold minerals from the gold deposits are native gold with minor electrum and calaverite. The form and grain size of gold minerals from the representative gold deposits reflect the metallogenic properties of medium-deep and medium-high temperature deposits. The projected gold fineness of the Xiaoyingpan gold mine all falls in the medium-temperature area in the figure and tends to be in the high-temperature area, while that of the Zhangquanzhuang gold mine mostly falls in the middle-temperature area, showing the difference in the metallogenic conditions of the two deposits. Both Xiaoyingpan and Zhangquanzhuang gold deposits show the following rules: poor in Zn, Pb, Sb and Se, but rich in Cu, Fe without Mn, indicating that both deposits are of medium-deep origin. The three representative gold deposits all show high gold fineness characteristics, and the general rules are as follows: Dongping-type gold deposit (934.8-969.7) > Xiaoyingpan-type gold deposit (900.0) > Zhangquanzhuang type gold deposit (824.0), showing that the representative gold deposits were formed at higher temperature and deeper depth, and the gold in the ores inherited the characteristics of high gold fineness originating from the Archean metamorphic rock series, which implying that the metallogenic material originated from the ancient metamorphic rock series; the long metallogenic period and multiple metallogenic stages made gold fully transformed, purified and enriched. There are three main occurrence states of gold minerals in the study area, from primary to secondary, they are respectively inclusion gold, gold minerals between other mineral crystals and those filled in the fractures of other minerals.